Old Testament exegesis a primer for students and pastors - Stuart, Douglas K. (Philadelphia, PA Westminster, 1984)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. -- hermeneutics; Bible. O.T. -- homiletcal use; Bible. O.T. -- bibliography